2020
DOI: 10.48550/arxiv.2006.06678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraints from gravitational wave detections of binary black hole mergers on the $^{12}\rm{C}\left(α,γ\right)^{16}\!\rm{O}$ rate

Robert Farmer,
Mathieu Renzo,
Selma de Mink
et al.

Abstract: Gravitational wave detections are starting to allow us to probe the physical processes in the evolution of very massive stars through the imprints they leave on their final remnants. Stellar evolution theory predicts the existence of a gap in the black hole mass distribution at high mass due to the effects of pairinstability. Previously, we showed that the location of the gap is robust against model uncertainties, but it does depend sensitively on the uncertain 12 C (α, γ)16 O rate. This rate is of great astro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 126 publications
3
51
0
Order By: Relevance
“…It is necessary to consider this hierarchical merger channel when using catalogs of GW sources to make inferences about the physics of black hole formation. For example, inference of the location of the lower edge of the pair-instability mass gap, which could potentially constrain nuclear reaction rates (Farmer et al 2020) or beyond Standard Model physics (Croon et al 2020;Straight et al 2020), using detections of black holes in the 50M regime would be contaminated by the presence of 2G black holes. In order to distinguish between 1G and 2G black holes, we must account simultaneously for the shapes of 1G and 2G populations and the relative frequencies of hierarchical mergers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to consider this hierarchical merger channel when using catalogs of GW sources to make inferences about the physics of black hole formation. For example, inference of the location of the lower edge of the pair-instability mass gap, which could potentially constrain nuclear reaction rates (Farmer et al 2020) or beyond Standard Model physics (Croon et al 2020;Straight et al 2020), using detections of black holes in the 50M regime would be contaminated by the presence of 2G black holes. In order to distinguish between 1G and 2G black holes, we must account simultaneously for the shapes of 1G and 2G populations and the relative frequencies of hierarchical mergers.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the GWTC-2 systems there are highmass BBHs which have components with masses of 45M (Abbott et al 2020a), the most massive being the source of GW190521 (Abbott et al 2020c). Black holes of ∼ 45-135M are not typically expected to form via standard stellar evolution as the pair-instability process either limits the maximum mass of the progenitor star's core or completely disrupts the star entirely (Fryer et al 2001;Heger & Woosley 2002;Belczynski et al 2016;Spera & Mapelli 2017;Stevenson et al 2019;Farmer et al 2019Farmer et al , 2020. Potential (non-mutually exclusive) formation mechanisms for black holes in this mass gap include hierarchical mergers, where the remnant of a previous merger becomes part of a new binary (Miller & Hamilton 2002;Antonini & Rasio 2016;Rodriguez et al 2019;Yang et al 2019;Banerjee 2020;Fragione & Silk 2020;Mapelli et al 2020a;Anagnostou et al 2020); stellar mergers, which may result in a larger hydrogen envelope around a core below the pairinstability threshold (Spera et al 2018;Di Carlo et al 2019;Kremer et al 2020); formation of black holes from Population III stars which are able to retain their hydrogen envelopes (Farrell et al 2020;Kinugawa et al 2020;Vink et al 2020), formation via stellar triples in the field (Vigna-Gómez et al 2020), or growth via accretion in an active galactic nucleus (AGN) disk (McKernan et al 2012;Secunda et al 2020;Tagawa et al 2020;Tiwari & Fairhurst 2020).…”
Section: Introductionmentioning
confidence: 99%
“…If such massive stars exist, this would result in a population of BHs "above the gap" with masses 120M . 38,39 Farmer et al 40,41 found that pair instability creates a mass gap in the BH mass spectrum starting at m 45M . This threshold was found to be a relatively solid prediction given the current understanding of stellar evolution.…”
Section: Masses: Populating the Pair-instability Mass Gapmentioning
confidence: 99%
“…These updates on position of lower edge of the upper mass gap were the result of detailed considerations of stellar evolution processes (e.g., rotation, mixing, convection) that allow some stars to avoid the PPSN/PSN. Finally, it was shown that for low metallicity stars (Z = 10 −5 ), the uncertainties in the reaction rate of carbon burning can potentially shift the onset of the BH upper mass gap up to 90 M (Farmer et al 2020). This reaction rate concerns one of the most uncertain reactions used in stellar evolution and yet it plays really important role in astrophysics (deBoer et al 2017;Takahashi 2018;Holt et al 2019;Sukhbold & Adams 2020).…”
mentioning
confidence: 99%